Desmoid Tumor About 3 Cases and Revue of Literature - Elatiqi, Oumkeltoum; Zinedine, Ismail; Aitbenlassal, Oumnia; Idelkhir, L.; Elamrani, Moulay Driss; Benchamkha, Yassine (International Journal of Innovative Research in Medical Science, 2023)
Desmoid tumors or aggressive fibromatosis are rare, recurrent, non-metastasizing tumors, developing from muscle fascias and aponeuroses, before surgery was the main treatment, with the latest recommendations and in view of the high risk of recurrence, the treatment consists of close monitoring, surgery is indicated if there are complications related to the location of the lesion. We report three observations of three young patients with desmoid tumors, one in abdominal location measuring 20/15cm in diameter invading the muscular wall and the peritoneum, the second at the level of the lower limb in the posterior face of the thigh and the right buttock measuring 30cm/10cm in diameter and the third one is abdominal too measuring about 20cm/15cm of diameter invading the peritoneum in a patient operated for rectal adenocarcinoma with familial adenomatous polyposis. The reason for consultation in the 3 patients was pain. After multidisciplinary consultations (surgeons, oncologist and radiotherapists) it was decided to perform surgical excision of the tumors, the follow-up is estimated at 25 months for the first abdominal location, 10 months for the location in the lower limb and 2 months for the third case, without noticing any recurrence, no adjuvant treatment was offered to the patients only close surveillance. Surgery for desmoid tumors is a double-edged sword given the high risk of recurrence which can only be decided after multidisciplinary consultations.